Unleashing the Potential for Promoting Socioeconomic Development in Africa: The Role of Intelligence Services - Mallya, Emmanuel (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
During the pervasive and protracted Cold War, states developed intelligence services as secret organisations to achieve international prominence and resist foreign influence domestically. Parallel to the globalisation process, states’ intelligence agencies are expanding far beyond military exercises to encompass intelligence collection, safeguarding persons and information, defining and authorising sanctions for infractions, and establishing the standards for unconstitutional conduct. Nonetheless, a common perception of contemporary African intelligence organisations is that they are essentially extensions of the occasionally autocratic government under which they operate. This allegation is based on the apparent access, power, and influence of African intelligence and security services by both domestic and international actors. This paper examines the role of intelligence services in encouraging social and economic growth in Africa. In this study, context and historical analysis research methodologies are used in both primary and secondary sources. This paper relates the issue with African intelligence services to their colonial origins. This work also reveals the delicate image of intelligence services in Africa and the issue of global infiltration. This article argues that African intelligence services, like their western counterparts, must live up to their obligation to safeguard Africa politically and economically. This highlights the necessity for African intelligence agencies to contribute to political stability through the development of several channels. This work proposes a strategic reorganisation of the intelligence agencies in order to enhance their image and efficacy in supporting the socioeconomic development of the continent.